Verifying β-Convergence for Chosen Regions of Indonesia - Blaško, M (KnE Social Sciences, 2018)
Abstract The convergence in the economy means the process of balancing disparities chosen indicators of homogeneous economic groups. In this article, we verify convergence through the Least Squares Method for 11 chosen regions of Indonesia. Used variables are the real GDP per capita and the average salary per capita in every chosen region of Indonesia between 2012 and 2015. We create dependence between the growth of GDP per capita and logarithm of GDP per capita in 2012. For complete explanation of the model and calculation of consistent, minimal estimator, we use dummies and create a structural parameter, which eliminates shocks and possible disparities between regions. Keywords: β-convergence, GDP per capita, Least Squares Method